Stop cyberbullying! - Ab Rashid, Siti Nursyuhada (Universiti Teknologi MARA, Perak, 2022)
Stop Cyberbullying is a campaign by Malaysian Communication and Multimedia Commision (MCMC) to encouraging people’s awareness towards cyberbullying issue in Malaysia. This campaign aims to provide awareness on cyberbullying to all parties and society.